THE QUALITY OF STEAM-PjBL MIND MAPPING SKILLS FOR PROSEPECTIVE ELEMENTARY SCHOOL TEACHERS - Muskania, Ricka Tesi; Kartono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study seeks to evaluate the quality of mind mapping generated by prospective elementary school teachers within the framework of project-based learning utilizing the STEAM (Science, Technology, Engineering, Arts, and Mathematics) methodology. Mind mapping serves as a technique to illustrate students' comprehension and concepts in the development of interdisciplinary learning projects. The evaluation emphasizes four primary aspects: the precision of interdisciplinary integration, the appropriateness of the project, the novelty of the concept, and the clarity of the visualization. This study employs a descriptive qualitative methodology, utilizing documentation and content analysis tools to examine students' mind mapping outputs following their engagement in STEAM-PjBL learning. The study's results show that most participants successfully integrated multiple scientific disciplines; however, they identified deficiencies in concept originality and visualization clarity. These findings offer significant insights into prospective instructors' preparedness to create interdisciplinary learning and establish a basis for enhancing future training methodologies.